The 500 hats of Bartholomew Cubbins - Geisel, Theodor Seuss 1904- (Vanguard Press, 1938)
At first, Bartholomew Cubbins had just one hat, but when the King ordered him to take it off, he found that he cound not--each time there was another on his head.